Interactive Game Application Themed "Perang Puputan Klungkung" - Putu Satria Udyana Putra; Mochamad Arman Efendi; Putu Wirayudi Aditama; Dwi Novitasari; I Nyoman Anom Fajaraditya Setiawan (Jurnal Mantik, 2022)
This study intends to educate those unfamiliar with the history of the war puputan klungkung. According to the results of the questionnaire sent to 40 respondents, 77.5% were unaware of the history. The proposed approach is to introduce the history of the “Perang Puputan Klungkung” through interactive game media, as both children and adults are avid gamers. The stages of research include data gathering, data analysis, design, media format, and testing. The stage of data collection involves gathering information about the Klungkung puputan war. The stage of data analysis consists of analyzing the previously collected data. The design phase consists of selecting the concept, generating assets, text, audio, and navigation menu structures. The Stage of Media Forms that combines everything created in the Design Stage. The testing phase of blackbox testing consists of five test scenarios that result in the game's functionality functioning as planned.